Near rectilinear orbits around the moon as operational orbit for the future deep space gateway - Sánchez Lara, Carlos; Sánchez Cuartielles, Joan Pau (European Space Agency (ESA), 2018)
The aim of this paper is to revise the suitability of Near- Rectilinear Halo Orbits (NRHOs) as long-term destinations for a new crew-tended space station; referred here as Deep Space Gateway (DSG). NRHOs are a subset of the halo families characterized by promising stability properties. The document presents the formal definition and identification of NRHOs, as in the CR3BP model. Dynamical substitutes of the NRHOs are also refined in the Bi-Circular Model (BCM) by means of a multiple shooting method. Key features such as lunar south-pole coverage, station keeping requirements and accessibility of the orbit are then analysed. Several maintenance strategies based on three different underlying principles are considered and, finally, the accessibility of NRHOs from the Earth and polar Moon orbits is investigated.
Keywords: NRHO; DSG; Station keeping; Cislunar space; Differential corrections